Glutamine supplementation in oncology : a systematic review - Van Zyl, Elizma (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2010.